STRATEGI BISNIS WARUNG MAKAN LE ARJAN DALAM MEMPERKUAT DAYA SAING DAN PROFITABILITAS PADA PASAR KULINER YANG KOMPETITIF DI KOTA GORONTALO - Mokodompit, Nur Eng; Mohamad, Salma (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2024)
The research objectives are to: 1) identify factors that influence the competitiveness of restaurants in the competitive culinary market, 2) To evaluate strategies that can increase the competitiveness of restaurants in the culinary market, 3) To analyze the factors that influence sales of products and services in restaurants, and 4) To formulate strategies that can increase sales of products and services in restaurants. Data collection techniques are carried out through interviews, observation and documentation. The research results show that Warung Makan Le Arjan faces challenges in food business development and competitiveness. In identifying the right strategy, SWOT analysis is used to evaluate the strengths, weaknesses, opportunities and threats that influence it. The analysis results show that Warung Makan Le Arjan has strengths in product quality, positive reputation, and accessibility, but faces weaknesses in dependence on certain raw materials and lack of technology adoption. There are opportunities in increasing public interest in spicy food and word of mouth promotion, but also threats from intense business competition and fluctuations in raw material prices. Based on the results of the analysis, suggestions were given to Warung Makan Le Arjan, including focusing on improving product quality, diversifying raw material supplies, and encouraging technology adoption. Collaboration with external parties and infrastructure development are also recommended.